Digamasellid mites (Acari: Mesostigmata) in association with saproxylic darkling beetles (Coleoptera: Tenebrionidae) and wood-decaying fungi (Polyporales) in Slovakia - Mašán, Peter (Zootaxa, 2025)
Three species of digamasellid mites adapted to life in wood-decaying polypore fungi and phoretically associated with saproxylic and fungivorous beetles of the family Tenebrionidae are described from adult and deutonymphal stages from forest habitats in Slovakia. Two of the mites are described as new species: Bulbolaelaps neomidae sp. nov., the second member of the genus, whose developmental stages were previously unknown, is specifically associated with the tinder fungus Fomes fomentarius (L.) Fr., and its deutonymphs are phoretically dispersed by the beetle Neomida haemorrhoidalis (Fabricius); Insectolaelaps diaperi sp. nov. inhabits various non-perennial polypores infested by the beetle Diaperis boleti (Linnaeus), whose adults serve as a specific host for the phoretic deutonymphs. The third species described, Insectolaelaps latopini (Hirschmann & Wiśniewski, 1982), lives in various perennial polypores, mainly in Fomes fomentarius, which it colonises by phoresy on the black tinder beetle Bolitophagus reticulatus (Linnaeus), but also occasionally on other host species such as Bolitophagus interruptus Illiger and Eledonoprius armatus (Panzer). Each mite exhibits at least one unique morphological feature that is rare or absent in the Digamasellidae: the females of B. neomidae have only three pairs of setae on the sternal shield, the deutonymphs of I. diaperi have only two pairs of setae on the sternal shield, and I. latopini possesses only one anterolateral seta on the genu and tibia of legs III.